2010
DOI: 10.3390/md8112810
|View full text |Cite
|
Sign up to set email alerts
|

Recent N-Atom Containing Compounds from Indo-Pacific Invertebrates

Abstract: A large variety of unique N-atom containing compounds (alkaloids) without terrestrial counterparts, have been isolated from marine invertebrates, mainly sponges and ascidians. Many of these compounds display interesting biological activities. In this report we present studies on nitrogenous compounds, isolated by our group during the last few years, from Indo-Pacific sponges, one ascidian and one gorgonian. The major part of the review deals with metabolites from the Madagascar sponge Fascaplysinopsis sp., nam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…Alkaloids, regarded as basic plant derived metabolites, are important components of plant defence, growth and development systems [50] , [51] . In a study of sponges and ascidians, an abundance of alkaloids was reported that displayed biological activities such as metabolites [52] . Considering the omnivorous dietary habit of M .…”
Section: Resultsmentioning
confidence: 99%
“…Alkaloids, regarded as basic plant derived metabolites, are important components of plant defence, growth and development systems [50] , [51] . In a study of sponges and ascidians, an abundance of alkaloids was reported that displayed biological activities such as metabolites [52] . Considering the omnivorous dietary habit of M .…”
Section: Resultsmentioning
confidence: 99%
“…Kashman et al [ 48 ] isolated the salarins from the extracts of Fascaplysinopsis sp., a marine sponge collected from Salary Bay in Madagascar. These sponges contained four groups of nitrogenous macrolides, salarins (A–J), tulearins (A–C), taumycins (A and B), and tausalarins (C), which consist of a combination of taumycin and salarin.…”
Section: Marine Anticancer Molecules Reported In 2012mentioning
confidence: 99%
“…We became interested in (+)-taumycin A as a synthetic target due to its biological activity and several unique structural elements including, but not limited to, its two isoleucine residues and the unique 1,6-diene, decorated with a chirality center and two E-olefins, one of which is conjugated to the C5 position of a monosubstituted oxazole. 5 Also of note, unlike larger ring examples, 12-membered macrolides 6 remain relatively uncommon in the natural product literature, with depsipeptides comprising an even smaller subset of these compounds. 7 To help quantitate this last statement, after an exhaustive search of the literature, we were only able to find a few examples of 12-membered depsipeptides, which include tausalarin C (5), 7a especially notable here since it is biosynthetically related to taumycins A and B (Figure 2).…”
Section: ■ Introductionmentioning
confidence: 99%
“…7 To help quantitate this last statement, after an exhaustive search of the literature, we were only able to find a few examples of 12-membered depsipeptides, which include tausalarin C (5), 7a especially notable here since it is biosynthetically related to taumycins A and B (Figure 2). Other examples are noteworthy for separate reasons: Stereocalpin A 7b (6), confirmed by total synthesis, 7c,d is the only member of the series with two L-amino acids and an antirelationship at C(4)−C (5); hapalosin (7) 7e,f has a synrelationship at C(4)−C( 5), but its amino acid residues (L-Phe and L-Val) have been altered biosynthetically. The acremolide family (8−11) 7g has both D-and L-amino acid residues but has a β-hydroxy amide moiety in place of the 1,3carbonyl found in taumycins A and B.…”
Section: ■ Introductionmentioning
confidence: 99%